Impacts of Temporary Migration on Development in Origin Countries - Bossavie, Laurent; Özden, Çağlar (World Bank, Washington, DC, 2022)
Temporary migration is widespread globally. While the literature has traditionally focused on the impacts of permanent migration on destination countries, evidence on the effects of temporary migration on origin countries has grown over the past decade. This paper highlights that the economic development impacts, especially on low- and middle-income origin countries are complex, dynamic, context-specific and multi-channeled. The paper identifies five main pathways: (i) labor supply, (ii) human capital, (iii) financial capital and entrepreneurship, (iv) aggregate welfare and poverty, and (v) institutions and social norms. Several factors shape these pathways and their eventual impacts. These include initial economic conditions at home, the scale and double selectivity of emigration and return migration, and employment and human capital accumulation opportunities experienced by migrants while they are overseas, among others. Meaningful policy interventions to increase the development impacts of temporary migration require proper analysis, which, in turn, depends on high quality data on workers’ employment trajectories. This is currently the biggest research challenge to overcome to study the development impacts of temporary migration.